2019
DOI: 10.1177/1354816619843452
|View full text |Cite
|
Sign up to set email alerts
|

Terrorism and inbound tourism: Does immigration have a moderating effect?

Abstract: This article investigates the impact of terrorism on bilateral tourism flows within the Organization for Economic Co-operation and Development countries. It also examines the moderation effect of immigration in the destination country on the terrorism–tourism relationship. The results obtained from the estimated gravity models show that after reaching a certain threshold, terrorism negatively impacts tourist arrivals. This relation seems to be moderated by the share of immigrants in the country of destination:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…These results are echoed in recent work by Harb and Bassil (2020), investigating the impact of terrorism on tourism flows within the group of countries of the Organization for Economic Co-operation and Development. They also found an inverse U-shaped relationship: below a certain level, terrorism had a positive correlation with tourism, but beyond a certain threshold the relationship turned negative.…”
Section: Insecurity and Tourismmentioning
confidence: 89%
See 1 more Smart Citation
“…These results are echoed in recent work by Harb and Bassil (2020), investigating the impact of terrorism on tourism flows within the group of countries of the Organization for Economic Co-operation and Development. They also found an inverse U-shaped relationship: below a certain level, terrorism had a positive correlation with tourism, but beyond a certain threshold the relationship turned negative.…”
Section: Insecurity and Tourismmentioning
confidence: 89%
“…1 The new gold standard in gravity models includes structural forces or high-dimensional fixed effects in the specification to capture multilateral resistance terms (Anderson and Yotov, 2012; Fally, 2015). As discussed by Harb and Bassil (2020), bilateral tourism flows not only are determined by factors affecting the attractiveness of the destination country but also depend on the attractiveness of alternative destinations. This effect can be termed ‘multilateral resistance to tourism’ and can be controlled for by including source- and destination-specific year fixed effects as well as dyadic fixed effects in the PPML estimation procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Tourists may, however, be willing to accept the risk if the destination is exceptional enough to entice them (Frey, Luechinger, & Stutzer, 2007;Lepp & Gibson, 2003). In the same vein, a number of papers have shown that the effect of political instability/terrorism on tourism may be non-linear; that is, it starts adversely impacting tourism after reaching a certain threshold (Harb & Bassil, 2019;Mitra, Pham, & Bandyopadhyay, 2018;Saha & Yap, 2014). Sharifpour, Walters, and Ritchie (2013) and Morakabati and Kapu sci nski (2016) opine that risk appetite varies across tourist groups, from allocentric to psychocentric, and is mainly determined by the personality traits of tourists and the uniqueness of the destination.…”
Section: Tourism and Geopolitical Riskmentioning
confidence: 99%
“…The attacks on Brussels and Istanbul airports are, alongside the attacks at sites in several French cities, including Paris, different in that they directly involved foreign travellers (Harb and Bassil, 2019;Isaac and Velden, 2018;Lagrave, 2016;Liu and Pratt, 2017;Oliveira and Costa, 2018;Reuter et al, 2018). Further, such events have not only influenced tourists' behaviours in terms of preferred travel destinations and their overall pre-and postpurchasing behaviours but have also increased the perceived risk of travelling and decreased travel flexibility (Hsu et al, 2009).…”
Section: Tourism Crisesmentioning
confidence: 99%